Pengaruh Pemberian Fisioterapi Transcutaneous Electrical Nerve Stimulation (TENS) Terhadap Penurunan Nyeri pada Pasien Osteoarthritis Lutut di RS Hermina Tangkubanprahu - Sri Suwarti; Wiek Israwan; Amin Zakaria; Fransisca Xaveria Hargiani (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:  This study aims to prove Transcutaneous Electrical Nerve Stimulation (TENS) has an effect on reducing pain in knee osteoarthritis patients, as well as to prove acupuncture-like TENS is more effective compared to conventional TENS. Methods: The design  of this  study  is  quasi experimental with two groups pre and post test design. The study was conducted in August to  October 2021. Given    six treatments with the number of samples used thirty one respondents as an experimental group given acupuncture-like TENS and  thirty one respondents as a control group given conventional TENS taken from the results of pre-tests and post-tests that fit the inclusion criteria of this study.Results:  Measurement of pain with visual analogue scale (VAS). Using   the wilcoxon signed ranks test and obtained the results p<0.05 and mann-whitney test results on post-test results with a value of p = <0.05.  Conclusion:  Based on the results of statistical tests it can be concluded that TENS has an effect on reducing pain in knee osteoarthritis patients at Hermina Tangkubanprahu Hospital, and acupuncture-like TENS is more effective than conventional TENS.